Characterizing nanoscale pores and its structure in coal: Experimental investigation. Issue 4 (July 2019) - Zhao, Difei; Guo, Yinghai; Wang, Geoff; Mao, Xiaoxiao
One of the challenges in evaluating and estimating the gas storage and migration of coal has been the investigation of complex pore structures, especially in the nanoscale. The present study provides new insights into nanoscale pore types, and the genesis, classification, and structure characteristics of high-rank coal by investigating 10 anthracite coals in the Shanxi Formation and Taiyuan Formation of the Xinjing Coal Mine in the Qinshui Basin, North China. A series of experiments that combined the qualitative observation method of argon ion polishing technology in combination with field emission-scanning electron microscope and quantitative analysis methods of low-pressure N2 gas adsorption and mercury intrusion porosimetry were performed to characterize nanoscale pore structures and its influence on gas behavior. The results revealed that various types of nanoscale pores exist in the coal matrix. Descriptive classifications for nanoscale pores consist of three major groups (organic matter pores, mineral-related pores, and micro-fractures), and nine subtypes was summarized to correlate pores to the networks. Furthermore, mercury intrusion porosimetry, low-pressure N2 gas adsorption, and image processing were combined to determine the pore size distributions, indicating that pore sizes are bimodally distributed with two broad peaks. The major peak at approximately 20–400 nm was mostly associated with isolated microscopic organic constituents interparticle nanopores, while a minor but prominent peak at the macro-pore to micro-fracture scale was more associated with epigenetic pores, mineral-related pores, and micro-fractures. Furthermore, image processing also provides a specialized approach to reveal the structure and diameter of different types of nanoscale pores. The combination of quantitative test and qualitative observation indicate that different major pore types dominate each size range of reservoir space in coal. These results lead to a feasible assumption that the poor connectivity of nanoscale pores and lack of seepage channels between the nanoscale pores and fracture-cleat networks may have led to the low "micro-permeability" of the coal matrix, which affects the productivity of coalbed methane in high-rank coal.